Additional right renal veins: clinical implication - Jolly Agarwal; Virendra Kumar; Vandana Sharma (Academia Anatomica International, 2017)
Background: Each kidney is drained by single renal vein on each side. Right renal vein is shorter than left renal vein and both veins drain into inferior vena cava. The aim of our study is to find the variation in renal vasculature at the renal hilum. Methods: The present study was conducted on the 30 embalmed cadavers (20 males and 10 females) in the Department of Anatomy of SRMS IMS, Bareilly from 2006 to 2015. Results: The present study revealed the presence of two additional renal veins on the right side along with the normal right renal vein in one cadaver (3.33%). Conclusion: Therefore, it is crucial to understand the variation of renal vein as this is important for the designing of catheter, angiography, renovascular hypertension, treatment of renal trauma and renal artery embolization. Therefore, the variation of renal vein should be kept in mind during transplantation and to prevent bleeding by an accidental trauma when operating in the retroperitoneal region.